Spin dynamics of cold exciton condensates - Kyriienko, Oleksandr. (2013)
We analyze theoretically the dynamics of degenerate four-component condensates of cold indirect excitons. We account for both linear spin-dependent terms arising from spin-orbit interaction of Rashba and Dresselhaus types and nonlinear terms coming from the exciton-exciton interactions. We show that both terms should affect the dynamics of cold exciton droplets in real space and time and lead to the formation of a four-leaf polarization pattern as well as dips in the bright exciton density profile.